Exchange rates and Markov switching dynamics - Yin-Wong Cheung; Ulf G. Erlandsson (Center for Economic Studies and ifo Institute (CESifo), 2004)
This article presents a systematic and extensive empirical study on the presence of Markov switching dynamics in three dollar-based exchange rates. A Monte Carlo approach is adopted to circumvent the statistical inference problem inherent to the test of regime-switching behavior. Two data frequencies, two sample periods, and various specifications are considered. Quarterly data yield inconclusive evidence - the test rejects neither random walk nor Markov switching. Monthly data, on the other hand, offer unambiguous evidence of the presence of Markov switching dynamics. The results suggest that data frequency, in addition to sample size, is crucial for determining the number of regimes.
Keywords: F31; C22; 330; exchange rate dynamics; regime switching; Monte Carlo Test; sampling frequency; Wechselkurs; Overshooting; Kointegration; Schätzung; Preisniveau; Markovscher Prozess; Grossbritannien; Frankreich; Italien; Deutschland; regime switching